EFFECT OF NPK AND BIOFERTILIZERS ON PIGEON PEA ( TILIZERS ON PIGEON PEA (CAJANAS CAJAN L. MILL SP.) - L. P. DALAL; P. B. NANDKAR (The Bioscan, 2009)
Field trials were conducted in cotton black soil during the season 2001-02 and 2002-03. Response of Pigeon pea cultivar (Maroti var. IPCL-87119) to inoculation with Rhizobial strains was studied. Wild strains of Rhizobium sp.from Pigeon pea and Azotobacter chroococcum, Pseudomonas striata (Regional centre for organic farming, Nagpur) and its mix culture T4, T5 and T6 was performed significantly well in improving plant height, number of branches, and grains (seeds) yield of higher cost benefits and more additional net income as compared to NPK controls. It was further reported that T5 performed well with Pigeon pea cultivar (Maroti var. IPCL-87119) indicating its specificity.